Metal contact metamorphism and mineralization in Lunahuaná, Cañete - Medina, Rafael (2013)
The mean metamorphism at Quebrada Totorita, Lunahuaná, is “Contact Metamorphism”-type, according to the fieldwork, characterization of geological units and supported with thin sections petrography. A strong hydrothermal alteration of biotite was recognized associated to the metamorphism, although with very localized extension, which suggest a probable metallic occurrence of Porphyry Copper-Skarn.Key words: